Dynamics of Major Cereals Productivity in Nepal - Gairhe, Samaya; Shrestha, Hari Krishna; Timsina, Krishna (Journal of Nepal Agricultural Research Council, 2018)
Cereal crops have played major roles in addressing food security issues in Nepal. In recent years there have been fluctuations in crop production and demands situations due to various reasons. Thus, the present study aims to analyze the dynamics of major cereals productivity in Nepal from 1995 to 2014. Focus group discussions were done in mid-hills and tarai of Nepal in 2015. Percentage change, compound growth rate, annual rate of change, coefficient of variation, instability index were calculated to analyze results. The result shows that the area, production and productivity of major cereals had an increasing trend over the study period. The major factors contributing on productivity increase in cereal crops were irrigation facilities, use of improved and hybrid seeds, chemical fertilizer and better technical knowhow among the farmers. For effective adoption of research outputs to improve the productivity emphasis should also be given on promotion of public private partnership (PPP) in research and development.